2019
DOI: 10.1039/c9qo00965e
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-controlled chemoselective N-dealkylation-N-nitrosation or C-nitration of N-alkyl anilines with tert-butyl nitrite

Abstract: A metal-free, acid-free and chemoselective N-dealkylation-N-nitrosation or C-nitration of N-alkyl anilines has been developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 68 publications
0
9
0
Order By: Relevance
“…Guo et al reported the N -dealkylation/ N -nitrosation of tertiary aromatic amines using TBN in organic media . It was found that the nature of the solvent has a pivotal role in the chemoselectivity of the process because both N -nitrosation and C -nitration are plausible pathways in air.…”
Section: N–n Bond Formationmentioning
confidence: 99%
See 3 more Smart Citations
“…Guo et al reported the N -dealkylation/ N -nitrosation of tertiary aromatic amines using TBN in organic media . It was found that the nature of the solvent has a pivotal role in the chemoselectivity of the process because both N -nitrosation and C -nitration are plausible pathways in air.…”
Section: N–n Bond Formationmentioning
confidence: 99%
“…For the C -nitration, the NO 2 radical and substrate react through an electrophilic radical addition process (Scheme , path a). For N -dealkylation- N -nitrosation, the t BuO radical directly abstracts a hydrogen atom from the N-Me group providing an α-amino radical, which is immediately oxidized into an iminium intermediate that leads to formaldehyde and the corresponding secondary amine which can be nitrosated by TBN (Scheme , path b) …”
Section: N–n Bond Formationmentioning
confidence: 99%
See 2 more Smart Citations
“…Divergent synthesis is of great significance in organic synthetic chemistry , owing to the rapid acquisition of structurally diverse chemical scaffolds from the same starting materials, which has also been considered as a highly attractive synthetic strategy for the synthesis of heterocyclic compounds. , Generally, different products could be generated from the identical starting materials through the variation of functional groups, catalysts, solvents, additives, and ligands to switch the reaction pathways. This strategy provides an indispensable route to build a molecular library with maximum scaffold diversity. Therefore, the divergent synthesis of various scaffolds from easily available starting materials is urgently pursued and expected.…”
Section: Introductionmentioning
confidence: 99%